PERANCANGAN ULANG KERANJANG PETANI TEH UNTUK MENGURANGI RESIKO KELUHAN MUSCULOSKELETAL DISORDERS DI PT. PERKEBUNAN TAMBI UNIT PRODUKSI TANJUNGSARI - Simanjuntak, Risma Adelina; Oesman, Titin Isna; Pramuditya, Lalang (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2020)
PT. Tambi Plantation Tanjungsari Production Unit is a company engaged in tea processing. The process of picking tea leaves is the beginning of the tea production process. Tea farmers work to collect tea leaves using cut scissors and collect in baskets made of woven bamboo. The results of the Nordic Body Map (NBM) show the use of old baskets can cause complaints Musculoskeletal Disorders (MSDs). The purpose of this study is to calculate the total points of MSDs complaints when using old baskets, redesign new baskets, and compare the level of MSDs complaints when using old baskets and new baskets. Body mass index (BMI) is used to determine the nutritional level of workers and NBM is used to find out complaints felt by workers. A new basket redesign is based on anthropometric data with body dimensions measured including: hip width, shoulder height in a sitting position, chest thickness, and belly thickness. The results of the NBM calculations, the score received by workers is 600 points. The new basket of tea growers consists of two components: the frame and the container for the tea leaves. The frame component has a width of 31 cm, height 51 cm, length of the supporting container 34 cm, the distance between the place of the bearing and the supporting container is 10 cm, the distance of the bearing space is 5 cm, the distance of the shoulder strap is 5 cm. The components of the tea leaf container have a height of 53 cm, the length of the base side 33 cm x 33 cm, a diameter of 57 cm. Paired Sample T Test with a 95% confidence level, stated that there is a very significant difference in the total number of MSDs between using an old baskets and a new baskets.